2007
DOI: 10.2170/physiolsci.rp009307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cysteine Derivatives Administration in Healthy Men Exposed to Intense Resistance Exercise by Evaluation of Pro-Antioxidant Ratio

Abstract: Abstract:The aim of this study was to ascertain the influence of cysteine derivatives on pro-antioxidant equilibrium and to compare the antioxidant effectiveness of N-acetylcysteine, α-lipoic acid, and taurine by using Loverro's coefficient (pro-antioxidant ratio) in healthy men exposed to intensity-resistance exercise. Fifty-five men were randomly assigned to one of four groups: control (CON, placebo), N-acetylcysteine (NAC 1.8 g·day -1 , 3 days), α-lipoic acid (LIP 1.2 g·day -1 , 3 days), or taurine (TAU 3 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…protein carbonylation products (22). The Loverro's coefficient or POTAOX have also permitted to compare an affectivity of antioxidant supplementation (10,23). Recently, the use of P/A ratio enabled us to confirm the antioxidant action of α-lipoic acid compared with other sulphur containing compounds (23).…”
Section: Discussionmentioning
confidence: 99%
“…protein carbonylation products (22). The Loverro's coefficient or POTAOX have also permitted to compare an affectivity of antioxidant supplementation (10,23). Recently, the use of P/A ratio enabled us to confirm the antioxidant action of α-lipoic acid compared with other sulphur containing compounds (23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that taurine can protect against oxidative stress under various conditions (Zhang et al 2004;Redmond et al 1998;Qi et al 1995;Silva et al 2011) and act as an antiinflammatory agent (Huxtable 1992;Zembron-Lacny et al 2007;Miyamoto et al 2009;Silva et al 2011). Furthermore, several studies reported the beneficial effects of taurine administration not only in rats, but also in humans (Baum and Weiss 2001;Dawson et al 2002;Zhang et al 2004;Silva et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Taurine (2-aminoethanesulfonic acid) is an amino acid derived from cysteine metabolism and is involved in cell volume regulation, detoxification, and osmoregulation, membrane stabilization, intracellular calcium flux regulation, and antioxidant production due to its molecular structure (Huxtable 1992;Zembron-Lacny et al 2007;Miyamoto et al 2009;Silva et al 2011). It has been reported that taurine can protect against oxidative stress under various conditions (Zhang et al 2004;Redmond et al 1998;Qi et al 1995;Silva et al 2011) and act as an antiinflammatory agent (Huxtable 1992;Zembron-Lacny et al 2007;Miyamoto et al 2009;Silva et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…7 Several studies have reported that the supplementation with antioxidants is a good alternative for reducing the damage caused by exercise in athletes or non-athletes. 8,9 However, with respect to antioxidant supplementation and exercise-induced oxidative stress and tissue injury, a clear consensus in no way exists. Disparities in the literature regarding antioxidant supplementation and attenuation of oxidative damage are likely due to several factors including training status of the subject population, 10 dietary intake, 11 as well as the magnitude and duration of supplementation period.…”
Section: Introductionmentioning
confidence: 99%